(untitled) (Padmakanya Journal of Science and Technology, 2025)
Ecosystem services (ES) play a crucial role in supporting livelihood and fostering socioeconomic status of rural community. Economic valuation of ES perceived by community serves as a basis for data driven sustainable resources management and integrated decision making. This study estimates the value of provisioning services provided by the Bihani Community Forest (BCF) by using the market price method. The statistically determined sample size of 79 households was surveyed via systematic sampling method during January, 2024. The value of provisioning services received by household was found to be average equivalent to NRs. 50,720.25 per household per year; which was 9.27% of average income of NRs. 4, 96,528.10 per household per year. It also evaluates the value of ecosystem services provided from BCF by calculating willingness to pay (WTP) by Community Forest User Group (CFUG) member for regulating, supporting and cultural services through their physical and monetary contribution in the conservation and sustainable management of the CF. The average WTP for the conservation and sustainable management of CF was found to be NRs. 3,649.64 per households (HH) per year. The study revealed that 29.11% of HHs was willing to pay only via physical participation, whereas 70.89% of HHs was willing to pay via both physical participation and monetary values. To assess the influence of various independent variables into WTP; multiple linear regression model with natural logarithm transformation was designed, which indicated that the time to reach CF and Family size are statistically significant predictors of WTP. The community forestry practice in BCF, Sarlahi has proven to be beneficial by providing various provisioning, regulating and aesthetic services that contributes to their livelihood and wellbeing. Additionally, the transfer of forest management responsibility to local community has promoted improved conservation and sustainable management of forest ecosystems.